Parental perceptions of the food environment and their influence on food decisions among low-income families: a rapid review of qualitative evidence - Divya Ravikumar; Eleni Spyreli; Jayne Woodside; Michelle McKinley; Colette Kelly (BMC, 2022)
Abstract Background The food environment within and surrounding homes influences family dietary habits with socio-economic areas at a nutritional disadvantage. Families' perception of the food environment and how it influences their food decisions is less clear. This rapid review aimed to synthesise qualitative evidence of parental perspectives of the food environment and their influence on food decisions among disadvantaged families. Method Qualitative and mixed-methods peer-reviewed journal articles published after 2000, that explored the perspectives of low-income parents in relation to their food environment and how this impacted food decisions for families with children aged 2-17 years, were included in this review. Embase, Scopus and PsycINFO were the databases chosen for this review. Search strategies included seven concepts related to family, food, perceptions, influences, environment, socio-economic status and study type. Two independent reviewers screened sixty-four studies. Thematic synthesis was employed. Results Two thousand one hundred and forty five results were identified through database searching and 1,650 were screened. Fourteen articles that originated from the US, Australia and the UK were included in this review. No articles were excluded following quality appraisal. Child preferences, financial and time constraints, and location and access to food outlets were barriers to accessing healthy food. Parental nutrition education and feeding approaches varied but positive outcomes from interventions to address these behaviours will be short-lived if inequities in health caused by poverty and access to affordable and healthy food are not addressed. The reliance on social support from families or government sources played an important role for families but are likely to be short-term solutions to health and nutritional inequities. Conclusions This qualitative evidence synthesis provides an insight into the perceptions of low-income parents on the factors influencing food decisions. Findings have implications for public health and the development of effective strategies to improve the dietary habits of children of disadvantaged families. Sustainable changes to dietary habits for families on low-income requires policy responses to low income, food access and to the high cost of healthy foods.